Pengelolaan Jenjang Karir Karyawan Melalui Aplikasi Web Menggunakan Metode Prototype di Pintex Cirebon - Nana Suarna; Nining Rahaningsih; Saeful Anwar (Jurnal Accounting Information System (AIMS), 2020)
Career path and supervision of employee work performance are the main elements in managing human resources for employees, and as a process that aims to improve the career of the workforce in accordance with their talents and abilities, so that they can function properly and optimally for the company. In managing employee career paths at Pintex, many employees do not meet the qualifications so that it can hamper the development of career paths for employees. Based on these problems in managing career levels of employee performance using the prototype method. Through this method it is expected to facilitate the process of assessing employee performance better and easier. he results of this study, are expected to help and facilitate the management of employee career paths, with the hope of improving employee performance in the company.